Exploring Factors Associated With the Motivation of Clinical Pharmacists: A Focus on the South African Context - Crafford, Lucille; Wouters, Anouk; Bronkhorst, Elmien; Gous, Andries G. S.; Kusurkar, Rashmi A. (Frontiers in Medicine, 2021)
Pharmacy practice in many middle to low- income countries has slowly transitioned from being product-focused to a more patient-focused clinical practice. Lack of motivation is one of the factors contributing to the scarcity of pharmacists in the wards. As little is known about motivation in clinical pharmacists, this study aimed to obtain insight into the quantity and quality of their work motivation and factors associated with it. Self-determination Theory, used as the framework, describes autonomous motivation as being generated from within or through personal endorsement and controlled motivation as originating from external factors. An online questionnaire including the Academic Motivation Scale to measure autonomous motivation, controlled motivation and amotivation, was sent to clinical pharmacy graduates across South Africa, followed by interviews to explain some results. Independent t-test was used to analyze differences in motivation of clinical pharmacists to perform clinical services based on personal and environmental factors. Interview data were transcribed and analyzed to explain significant quantitative findings. Higher amotivation was found in graduates who are currently not practicing in dedicated clinical pharmacist positions, as well as in graduates who do not receive additional financial benefits for clinical services. We found no significant differences in the work motivation of clinical pharmacists based on their gender, age, current practice setting, work experience and additional training received. The interviews revealed that relatedness and autonomy are the most important factors for clinical pharmacists’ work motivation. Overall participants had a high mean autonomous motivation, a high mean controlled motivation and low mean amotivation. In line with Self-determination Theory literature, considering the basic psychological needs for relatedness and autonomy could assist with designing interventions, like creating a supportive work environment, to optimize motivation. This could improve professional wellbeing, service implementation and prevent possible adverse events. Future research is necessary to understand barriers and facilitators of clinical pharmacists’ work motivation.